Multiple Pulse Resonantly Enhanced Laser Plasma Wakefield Acceleration - Corner, L; Walczak, R; Nevay, L; Dann, S; Hooker, S; Bourgeois, N; Cowley, J (2012)
We present an outline of experiments being conducted at Oxford University on multiple-pulse, resonantly-enhanced laser plasma wakefield acceleration. This method of laser plasma acceleration uses trains of optimally spaced low energy short pulses to drive plasma oscillations and may enable laser plasma accelerators to be driven by compact and efficient fibre laser sources operating at high repetition rates. © 2012 American Institute of Physics.